Madjlis Ahli Soennah Garoet: Local Islamic Puritanism Movement and Its Roles in West Java during the Colonialism Era of 1926 – 1942 - Fauzan, Pepen Irpan; Fata, Ahmad Khoirul (Journal of Al-Tamaddun, 2022)
This article discusses the local Islamic puritanism movement in Tatar Sunda (West Java), namely Madjlis Ahli Soennah (MAS) Garoet. At the beginning of the 20th century, Persatuan Islam (Islamic Union or PERSIS) largely focused on organization with A. Hassan Bandung as its central figure and neglected local organizations. However, local organizations, such as MAS Garoet, similarly have significant roles in spreading the puritanism ideas in West Java. This study employed a combination of library research and in-depth interviews with social-scientific history to describe the MAS Garoet organization and its efforts to spread the puritanism ideas in West Java. This study aims to reveal the relationship between MAS Garoet and PERSIS because both had a similar ideology. It shows that MAS Garoet more effectively spread the Islamic puritanism ideas because most of its leading figures were native Sundanese who spoke Sundanese language fluently. PERSIS showed the opposite condition because the majority were non-Sundanese. Therefore, MAS Garoet served as an extension of PERSIS whose ideas were translated and spread to all areas of West Java.